2010
DOI: 10.1088/0022-3727/43/42/425404
|View full text |Cite
|
Sign up to set email alerts
|

A study of low temperature mechanical properties and creep behaviour of polypropylene using a new sub-ambient temperature nanoindentation test platform

Abstract: Mechanical properties and creep behaviour of an atactic-polypropylene (aPP) have been studied in the vicinity of its glass transition temperature (-18ºC) via a nanoindentation platform integrated with a sub-ambient temperature capability. All low temperature tests were validated by measurements on a fused silica reference sample from 25ºC to -30ºC. The fused silica results showed virtually invariant elastic modulus with temperature over this range consistent with literature measurements by sonic resonance. Har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Using dual cooling control Chen et al reported the development of a prototype cold stage accessory for the NanoTest demonstrating its ability to investigate the local mechanical properties and the creep behavior of atactic polypropylene down to -30ºC [135]. The cooling system used incorporated a purging chamber to eliminate condensation during cooling and two Peltier coolers to achieve the isothermal contact.…”
Section: Sub-ambient Temperature Nanoindentation Nano-scratch and Namentioning
confidence: 99%
“…Using dual cooling control Chen et al reported the development of a prototype cold stage accessory for the NanoTest demonstrating its ability to investigate the local mechanical properties and the creep behavior of atactic polypropylene down to -30ºC [135]. The cooling system used incorporated a purging chamber to eliminate condensation during cooling and two Peltier coolers to achieve the isothermal contact.…”
Section: Sub-ambient Temperature Nanoindentation Nano-scratch and Namentioning
confidence: 99%
“…Equation 2 has proved successful in interpreting loading rate effects and in determination of the strain rate sensitivity, a dimensionless creep parameter that exhibits some correlation with tan delta, 20,28,29 and in determination of glass transition temperatures occurring below 0 °C. 19 …”
Section: Nanoindentation Testingmentioning
confidence: 99%
“…19,29 The experimental creep depth data are closely fitted by the logarithmic Equation 2 enabling subtle changes in behavior to be determined. Tests at room and elevated temperatures on a range of amorphous to the improved initial creep compliance, and constraint did not occur.…”
Section: Indentation Creep Analysismentioning
confidence: 99%
See 2 more Smart Citations